1997
DOI: 10.1074/jbc.272.38.23645
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the Ecto-ATPase and Ecto-apyrase in Chicken Gizzard and Stomach

Abstract: We have examined the in vivo localization of extracellular ecto-ATPase and ecto-apyrase (ATPDase) in adult chicken gizzard and stomach by immunofluorescence and laser scanning confocal microscopy. In chicken gizzard, the ecto-ATPase was distributed in discrete clusters restricted to the sarcolemma of the smooth muscle cells. Anti-ecto-apyrase antibody detected a single 80-kDa band (putative apyrase) in Western blots of both chicken gizzard membrane extracts and partially purified anion exchange fractions, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…It differs from the ecto-ATPDases in that it does not hydrolyze ADP. Immunohistochemical studies further showed that although both ecto-ATPase and ecto-ATPDase are present in the chicken stomach, they have distinctly different localization, implying possibly different functions (15). Nevertheless, the deduced amino acid sequence of the chicken gizzard ecto-ATPase revealed significant sequence homology to that of CD39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It differs from the ecto-ATPDases in that it does not hydrolyze ADP. Immunohistochemical studies further showed that although both ecto-ATPase and ecto-ATPDase are present in the chicken stomach, they have distinctly different localization, implying possibly different functions (15). Nevertheless, the deduced amino acid sequence of the chicken gizzard ecto-ATPase revealed significant sequence homology to that of CD39.…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of the cDNA was amplified by polymerase chain reaction (PCR) using AmpliTaq DNA polymerase (PE Applied Biosystems, Foster City, CA) with 1 M primers and 2 mM MgCl 2 . Degenerate oligonucleotides, 5Ј-ATGGAR-TAYAARGGNAARGT-3Ј (sense, NH1, nucleotides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] corresponding to the amino acid sequence of the NH 2 -terminal peptide, MEYKGKV, and 5Ј-RAARTCNACNGGRAAYTC-3Ј (antisense, NH4, nucleotides 465-448) corresponding to the amino acid sequence of the internal peptide, EFPVDF, were used as primers. The reaction mixture was heated for 2 min at 95°C before addition of the Taq polymerase, followed by thermal cycling at 95°C for 45 s, 47°C for 30 s, and 70°C for 3 min for 4 cycles; then 95°C for 45 s, 53°C for 30 s, 70°C for 3 min for 30 cycles; and last, 1 cycle at 95°C for 30 s, 53°C for 30 s and 70°C for 10 min.…”
Section: Nh 2 -Terminal and Tryptic Peptide Sequence Determination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…of P i /min/mg) is lower than that of the digitonin-solubilized rat lung ectoapyrase (ϳ1000 mol of P i /min/mg of protein) (39).…”
Section: Fig 4 Expression Of Wild Type and Mutant Ectoapyrases In Cmentioning
confidence: 99%
“…Second, sucrose density gradient sedimentation profiles of both the expressed ectoapyrase in COS-7 cells and the native ectoapyrases from LG2 cells (data not shown) are identical: ectoapyrase behaved as a tetramer after solubilization with digitonin, a detergent that has little effect on the enzymatic activity, and became monomeric after solubilization with Triton X-100, a detergent that inhibits the activity. It has been suggested that detergents may inactivate ectoapyrase by destabilizing an oligomeric state of the protein (33,34), and it has been reported that chicken gizzard muscle ecto-ATPase (34) and rat lung ectoapyrase (39) are disulfide-linked homotrimers and homodimers, respectively. However, this work is the first demonstration that the ectoapyrase is a noncovalent tetramer.…”
Section: Fig 4 Expression Of Wild Type and Mutant Ectoapyrases In Cmentioning
confidence: 99%